2022
DOI: 10.1099/ijsem.0.005290
|View full text |Cite
|
Sign up to set email alerts
|

Hymenobacter siberiensis sp. nov., isolated from a marine sediment of the East Siberian Sea and Hymenobacter psoromatis sp. nov., isolated from an Antarctic lichen

Abstract: Gram-stain-negative, strictly aerobic, red-pink-coloured, rod-shaped and non-motile bacterial strains PAMC 29290, PAMC 29294T and PAMC 29296 were isolated from marine surface sediment sampled in the East Siberian Sea and strains PAMC 26553 and PAMC 26554T were obtained from an Antarctic lichen. Strains PAMC 29290, PAMC 29294T and PAMC 29296 were closely related to Hymenobacter artigasi (98.8 % 16S rRNA gene similarity), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…The bacterial strain PAMC 29467 T was isolated from freshwater of the pond in Cambridge bay, Canada during a study on the physiological characterization of culturable bacteria from Arctic freshwater. Out of the 100 type strains of the genus Hymenobacter, 22 strains were obtained from air [2], glacier [5], lichens [2], marine sediment [1], red snow [1], rocks [4], and soils [7] of Antarctica or Arctic [1,6,7,13,16,20,36,40,53,64,72,79]. Thirteen strains of the genus Hymenobacter have been isolated from freshwater samples collected in Republic of Korea and Taiwan.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The bacterial strain PAMC 29467 T was isolated from freshwater of the pond in Cambridge bay, Canada during a study on the physiological characterization of culturable bacteria from Arctic freshwater. Out of the 100 type strains of the genus Hymenobacter, 22 strains were obtained from air [2], glacier [5], lichens [2], marine sediment [1], red snow [1], rocks [4], and soils [7] of Antarctica or Arctic [1,6,7,13,16,20,36,40,53,64,72,79]. Thirteen strains of the genus Hymenobacter have been isolated from freshwater samples collected in Republic of Korea and Taiwan.…”
Section: Introductionmentioning
confidence: 99%
“…The genus Hymenobacter encompassed 100 validly published species on LPSN (https://lpsn.dsmz.de/genus/hymenobacter) at the time of writing (December 2022) [2]. One hundred type strains of the genus Hymenobacter have been isolated from various samples including air, freshwater, freshwater sediment, glaciers, lichen, marine sediment, plant, sand, seawater, and soil collected in tropical to polar regions, wastewater and meat, implying that members of the genus Hymenobacter are successful colonisers in a wide range of environmental conditions (Table S1) [1, 3–84]. Type strains of the genus Hymenobacter are characterized as aerobic, rod-shaped, red-pink or pink-pigmented, Gram-stain-negative, and heterotrophic [6, 13, 20, 30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, Hymenobacter species frequently exhibit resistance to UV, cold temperatures and heavy metals. So far, a few Hymenobacter species have been obtained from plant tissues, including the bark of Ginkgo biloba [21], dry spikelet clusters of grass Setaria viridis [22] and Antarctic lichen [23]. In our previous study, Hymenobacter was found to be one of the dominant taxa in the microbial community of wheat leaves [24].…”
Section: Introductionmentioning
confidence: 99%